Toward Transparency : New Approaches and Their Application to Financial Markets - Vishwanath, Tara; Kaufmann, Daniel (Washington, DC: World Bank, 2014)
The Asian financial crisis in the late 1990s not only highlighted the welfare consequences of transparency in the financial sector but also linked this relatively narrow problem to the broader context of transparency in governance. It has been observed that objections to transparency, often on flimsy pretexts, are common even in industrialized countries. This article argues that transparency is indispensable to the financial sector and describes its desirable characteristics: access, timeliness, relevance, and quality. The authors emphasize the need to weigh the costs and benefits of a more transparent regulatory policy, and they explore the connection between information imperfections, macroeconomic policy, and questions of risk. The article argues for developing institutional infrastructure, standards, and accounting practices that promote transparency, implementing incentives for disclosure and establishing regulations to minimize the perverse incentives generated by safety net arrangements, such as deposit insurance. Because institutional development is gradual, the authors contend that relatively simple regulations, such as limits on credit expansion, may be the most reasonable option for developing countries. They show that transparency has absolute limits because of the lack of adequate enforcement and argue that adequate enforcement may be predicated on broader reforms in the public sector.